Red blood cell extracellular vesicles: new frontiers in hematological biomarker discovery - Joshi, Urja; George, Linz-Buoy; Highland, Hyacinth (Frontiers in Medicine, 2025)
Extracellular vesicles (EVs) offer promising opportunities in hematology for improved diagnostics, prognostics, and therapeutics, making them valuable tools in the molecular landscape. EVs derived from red blood cells (RBCs) are the primary source of EVs in the bloodstream. They perform several critical biological and physiological functions, such as facilitating intercellular communication and transferring biomolecules like DNA, RNA, and proteins. Hence, in this review, we aim to explore RBC-derived EVs and their potential as a diagnostic tool for their clinical relevance and associated biomarkers in hematology. Furthermore, we emphasized their crucial role in both physiology and disease. RBC-EVs are found to play a role in vascular damage, inflammation, and coagulopathy in several pathophysiological conditions, potentially influencing the progression of certain diseases. They also served as indicators for numerous conditions, including hereditary hematologic abnormalities, diabetes, and cardiovascular diseases. Hence, their importance lies in their ability to reflect and influence red cell health, immune responses, and systemic disease states as accessible, non-invasive indicators. Also, their composition mirrors the physiological or pathological state of RBCs and holds promise for both diagnostics and therapeutics.